Guidebook on the Development of Climate-Smart Maps and Adaptation Plans (CS-MAP) for Rice Production in Viet Nam - Le, Thanh Tung; Bui, Tan Yen; Pham, Thanh Van; Nguyen, Viet Khoa; Tran, Thi My Hanh; Nguyen, Van Hung; Bernardo, Eisen; Celeridad, Renz Louie V. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This guidebook explains how to develop and implement the Climate-Smart Map and Adaptation Plan (CS-MAP). Using participatory tools, CS-MAP serves as a guide for local communities to develop their own risk maps and adaptive plans, which cater to their respective local contexts.